Simultaneous Vascular Reconstruction and Cervical Anastomosis in McKeown Esophagectomy - Chen, Lei; Zhang, Jiaheng; Chen, Donglai; Sang, Yonghua; Yang, Wentao (Frontiers in Surgery, 2021)
A stomach was considered ineligible to be an ideal conduit conventionally if its right gastroepiploic artery (RGEA) were injured. However, both sufficient blood flow and good venous return are crucial to the success of reconstruction. And there lacks robust evidence regarding the surgical techniques of reconstructing RGEA and right gastroepiploic vein (RGEV) and performing cervical anastomosis with gastric conduit simultaneously. Herein, we summarized the key surgical techniques for simultaneous vascular reconstruction and gastric conduit anastomosis in McKeown esophagectomy.